School health promotion and use of drugs among students in Southern Brazil - Fernanda Marques Paz; Vanessa Andina Teixeira; Raquel Oliveira Pinto; Cristine Scattolin Andersen; Larissa Prado Fontoura; Luís César de Castro; Marcos Pascoal Pattussi; Rogério Lessa Horta (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE: To analyze the relationship between the health promotion conditions in schools and the consumption of alcohol and other drugs by students. METHODS: This is a cross-sectional study with a probabilistic sample of 3,464 students aged 12 to 17 from all schools of the cities of Lajeado and Sapiranga, state of Rio Grande do Sul, Brazil, and 53 managers from the same schools; the data was collected in 2012. Reports of the use of tobacco, alcohol, and illicit drugs in 2012 were used as outcomes, and the health promotion score in the school environment was used as the exposure of interest. We submitted the data to multilevel analysis. RESULTS: The prevalence of the annual use of tobacco was 9.8% (95%CI 8.8-10.8), alcohol was 46.2% (95%CI 44.5-47.8), and other drugs was 10.9% (95%CI 9.9-12.0). In the crude analysis, only the use of tobacco was associated with less health promoting schools (OR = 1.89, 95%CI 1.16-3.09) when compared to those with better conditions. This association lost statistical significance in the adjusted analysis (OR = 1.27, 95%CI 0.74-2.19). CONCLUSIONS: The effects of the school environment on the use of drugs, especially tobacco and alcohol, are manifested mainly by the individual and family conditions of the adolescents.